Science of Fungi in Grapevine - Viret, Olivier; Gindro, Katia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2025)
This open access book provides a comprehensive exploration of the relationship between fungi and grapevines, covering contemporary mycological classifications, pathogens, the mycobiome, endophytes, and mycorrhizae. Inspired by the French book "La Vigne, Maladies Fongiques" by the same authors, which won first prize at the 2015 OIV book competition (Organisation Internationale de la Vigne et du Vin, Dijon), this work aims to extend and update that foundational text. The introduction delves into the origins and adaptability of grapevines in response to evolving fungal diseases, alongside an overview of their biology, epidemiology, and control measures. The second chapter covers the systematics of the genus Vitis, the developmental stages of the vine, the anatomy of various organs, the history and breeding of resistant varieties, and the natural defense mechanisms of grapevines against fungal infections. A significant portion of the book provides the latest insights into mycology, including chapters on fungal systematics and taxonomy, as well as the concepts of holobiome, microbiome, and mycobiome in relation to grapevines. The third part focuses on fungal diseases affecting green organs, wood, and roots, illustrated at macroscopic, microscopic, and ultrastructural levels, and includes discussions on disease cycles and epidemiology. Additionally, there is a chapter dedicated to grafting systems and the specificity of fungi in nurseries. The final chapter addresses the control of fungal diseases, from historical perspectives to modern chemical groups of active ingredients, natural fungicides, and comprehensive disease management strategies. This includes application techniques, calibration of spraying equipment, drift reduction, and proper storage and handling of fungicides. This open access book serves as a key reference on the complex interactions between fungi and grapevines for scientists, students, and winegrowers, offering extensive practical knowledge and a rich scientific background based on over thirteen years of research by the authors.
Introduction -- Grapevine -- Grapevine mycobiote -- Fungal Diseases of Grapevine Green Parts -- Wood Diseases -- Root Diseases -- Grafting and Fungi in the Nursery -- Disease Control.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Plant diseases; Agriculture; Plant Pathology; Agriculture